2020
DOI: 10.1002/pds.5155
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the US FDA adverse event reporting system to identify adverse cardiac events associated with hydroxychloroquine in older adults

Abstract: Purpose: The purpose of this study is to analyze the US FDA Adverse Event Reporting System (FAERS) to identify adverse cardiac events of hydroxychloroquine in older adults. Method: A case/non-case method was used to determine adverse events associated with hydroxychloroquine as the primary suspect drug between January 1, 2004, and December 31, 2019, for older adults (≥65 years). Adverse events are preferred terms (PTs) defined in MedDRA. We used frequentist approaches, including the reporting odds ratio (ROR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
(56 reference statements)
1
1
0
Order By: Relevance
“…Similarly, an earlier study by Van Puijenbroek et al 43 found out that both PRR and ROR detected more disproportionate signals than IC. However, our study used more stringent thresholds for the frequentist methods (PRR and ROR lower 95% confidence interval of at least 2.0), consistent with recently published literature 44 . Our findings show that with improved signal detection thresholds, the specificity for frequentist methods can be improved (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, an earlier study by Van Puijenbroek et al 43 found out that both PRR and ROR detected more disproportionate signals than IC. However, our study used more stringent thresholds for the frequentist methods (PRR and ROR lower 95% confidence interval of at least 2.0), consistent with recently published literature 44 . Our findings show that with improved signal detection thresholds, the specificity for frequentist methods can be improved (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Although hydroxychloroquine and chloroquine are generally well-tolerated, they can have severe cardiologic adverse effects, including cardiomyopathy and conduction defects [13] . Furthermore, a recent survey from the United States Food and Drug Administration Adverse Event Reporting System indicated a relatively high risk of cardiomyopathy and myocardial disorders following exposure to hydroxychloroquine in older adults [21] . In contrast, the use of antimalarials was associated with a lower prevalence of CHF in our large multicenter retrospective SLE cohort, and, interestingly, this effect occurred independently of disease severity.…”
Section: Discussionmentioning
confidence: 99%